The Involvement of the Cas9 Gene in Virulence of Campylobacter jejuni - Shabbir, Muhammad A. B.; Tang, Yanping; Xu, Zihui; Lin, Mingyue; Cheng, Guyue; Dai, Menghong; Wang, Xu; Liu, Zhengli; Yuan, Zonghui; Hao, Haihong (Frontiers in Cellular and Infection Microbiology, 2018)
Campylobacter jejuni is considered as the leading cause of gastroenteritis all over the world. This bacterium has the CRISPR–cas9 system, which is used as a gene editing technique in different organisms. However, its role in bacterial virulence has just been discovered; that discovery, however, is just the tip of the iceberg. The purpose of this study is to find out the relationship between cas9 and virulence both phenotypically and genotypically in C. jejuni NCTC11168. Understanding both aspects of this relationship allows for a much deeper understanding of the mechanism of bacterial pathogenesis. The present study determined virulence in wild and mutant strains by observing biofilm formation, motility, adhesion and invasion, intracellular survivability, and cytotoxin production, followed by the transcriptomic analysis of both strains. The comparative gene expression profile of wild and mutant strains was determined on the basis of De-Seq transcriptomic analysis, which showed that the cas9 gene is involved in enhancing virulence. Differential gene expression analysis revealed that multiple pathways were involved in virulence, regulated by the CRISPR-cas9 system. Our findings help in understanding the potential role of cas9 in regulating the other virulence associated genes in C. jejuni NCTC11168. The findings of this study provide critical information about cas9's potential involvement in enhancing the virulence of C. jejuni, which is a major public health threat.